Evaluation of the Usage of Erythropoietin in Patients with End-Stage Chronic Kidney Disease Dialysis Cycle in Hanoi Nephrology Hospital - Do, Thi Hoa (H. : ĐHQGHN, 2020)
Treatment and control of anemia plays an important role in improving the quality and effectiveness of artificial kidney. The study was conducted on 61 patients who met the selection and were not included in the excluded criteria group. Collecting data from medical records using retrospective, descriptive, vertical follow-up method for 6 months. Data were processed using Microsoft Excel Office 2010 and R. The results showed that patients used both EPO alpha and EPO beta simultaneously. Rate of usage’s EPO beta accounted for 23%, alpha EPO was 77%. Lyophilized form (EPO alpha) is most commonly used. Starting from T3, Hb. averages treat. There were no abnormalities in blood pressure, white blood cell, platelets, and electrolytes.